Company information security management mechanisms for critical data protection - Ippolitov, Yevhenii; Kydriavskyi, Ivan; Balan, Alla; Dryzhakova, Dina; Iuriev, Ivan (My University, 2025)
The relevance of this study is determined by the growing need to protect company’s critical data from cyber threats, which is an important part of the information security strategy. The aim of the study is to assess the level of implementation of information security mechanisms among companies and determine the effectiveness of their application for data protection. The research employed the following methods: questionnaire surveys, comparative data analysis, and correlation analysis. The obtained results showed that the lack of regular monitoring (0) correlates with a high frequency of incidents (3.9, correlation -0.97), which confirms the insufficient cyber protection. The frequency of incidents has an inverse relationship with the level of technology implementation (-0.96), especially in construction, where modern solutions are almost not used. The level of response to incidents is positively correlated with the effectiveness of protection mechanisms (0.99), which proves the importance of a quick response to threats. The academic novelty of the study is the comparison of the levels of implementation of security policies in different sectors and determining the impact of the effectiveness of company information security management mechanisms on ensuring data security in the face of modern cyber threats. Research prospects include a deeper study of the impact of external and internal factors on the effectiveness of information security.
Keywords: information security; cyber threats; outsourcing; security policy; data protection; IT sector